Antenatal manifestations of inborn errors of metabolism: biological diagnosis. Issue 5 (8th July 2016) - Vianey‐Saban, Christine; Acquaviva, Cécile; Cheillan, David; Collardeau‐Frachon, Sophie; Guibaud, Laurent; Pagan, Cécile; Pettazzoni, Magali; Piraud, Monique; Lamazière, Antonin; Froissart, Roseline
Abstract: Inborn errors of metabolism (IEMs) that present with abnormal imaging findings in the second half of pregnancy are mainly lysosomal storage disorders (LSDs), cholesterol synthesis disorders (CSDs), glycogen storage disorder type IV (GSD IV), peroxisomal disorders, mitochondrial fatty acid oxidation defects (FAODs), organic acidurias, aminoacidopathies, congenital disorders of glycosylation (CDGs), and transaldolase deficiency. Their biological investigation requires fetal material. The supernatant of amniotic fluid (AF) is useful for the analysis of mucopolysaccharides, oligosaccharides, sialic acid, lysosphingolipids and some enzyme activities for LSDs, 7‐ and 8‐dehydrocholesterol, desmosterol and lathosterol for CSDs, acylcarnitines for FAODs, organic acids for organic acidurias, and polyols for transaldolase deficiency. Cultured AF or fetal cells allow the measurement of enzyme activities for most IEMs, whole‐cell assays, or metabolite measurements. The cultured cells or tissue samples taken after fetal death can be used for metabolic profiling, enzyme activities, and DNA extraction. Fetal blood can also be helpful. The identification of vacuolated cells orients toward an LSD, and plasma is useful for diagnosing peroxisomal disorders, FAODs, CSDs, some LSDs, and possibly CDGs and aminoacidopathies. We investigated AF of 1700 pregnancies after exclusion of frequent etiologies of nonimmune hydrops fetalis and identified 108 fetuses affected with LSDs (6.3 %), 29 of them with mucopolysaccharidosis type VII (MPS VII), and six with GSD IV (0.3 %). In the AF of 873 pregnancies, investigated because of intrauterine growth restriction and/or abnormal genitalia, we diagnosed 32 fetuses affected with Smith‐Lemli‐Opitz syndrome (3.7 %).